Ustavna ureditev in (ne)ustanovitev pokrajin v Sloveniji - Končan, Domen (Pravnik, 2023)
Despite the fact that the Constitution of the Republic of Slovenia has been establishing the constitutional foundations for a mandatory second tier of local self-government in Slovenia since the 2006 constitutional amendments, we are still waiting for legislative implementation. The prolonged legislator’s failure to comply with the constitutional obligation to enact the law about the establishment of regions violates Article 143 of the Constitution, the constitutional right to local self-government under Article 9, the rule of law principle under Article 2 and the separation of powers principle enshrined in Article 3(2) of the Constitution. However, as has been established in this article, the Constitutional Court will not be able to declare or sanction these violations due to the nature of the constitutional obligation to establish the second tier of local self-government and the separation of powers principle, both of which must be considered in constitutional adjudication. The discrepancy between the Constitution’s mandate for regions and the actual absence of regions, owing to an inability to achieve political consensus in the legislature on the constitutive law, is untenable in a rule-of-law state. Debates within the professional community often focus on potential changes to the Constitution; however, the issue surrounding regions is distinct. Despite the constitutional amendment’s overwhelming support from politicians and experts, it has not been translated into law, leaving all the inhabitants of Slovenia in a worse position than if the regions existed. The legislator should act as soon as possible to enact the law establishing the regions in accordance with the requirements of the Constitution and the fundamental principles of local self-government as derived from the European Charter of Local Self-Government.
Keywords: lokalna samouprava; pokrajine; pravna država; ustavno pravo; Ustavno sodišče; ustavnopravna obveznost; zakonodaja